Toxicity of malathion and lambda-cyhalothrin with piperonyl butoxide against the lesser grain borer, Rhizopertha dominica (University Journal of Zoology, Rajshahi University, 2008)
Key words: Toxicity, malathion, lambda-cyhalothrin, R. dominicaUniv. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 103-105